Obstetric Interventions Among Native and Migrant Women: The (Over)use of Episiotomy in Portugal - Elsa Lorthe; Elsa Lorthe; Elsa Lorthe; Milton Severo; Milton Severo; Milton Severo; Sousan Hamwi; Sousan Hamwi; Teresa Rodrigues; Teresa Rodrigues; Teresa Rodrigues; Cristina Teixeira; et al. (Frontiers Media S.A., 2024)
Objective: Episiotomy, defined as the incision of the perineum to enlarge the vaginal opening during childbirth, is one of the most commonly performed surgical interventions in the world. We aimed to determine if migrant status is associated with episiotomy, and if individual characteristics mediate this association.Methods: We analyzed data from the Bambino study, a national, prospective cohort of migrant and native women giving birth at a public hospital in mainland Portugal between 2017 and 2019. We included all women with vaginal delivery. The association between migrant status and episiotomy was assessed using multivariable multilevel random-effect logistic regression models. We used path analysis to quantify the direct, indirect and total effects of migrant status on episiotomy.Results: Among 3,583 women with spontaneous delivery, migrant parturients had decreased odds of episiotomy, especially those born in Africa, compared to native Portuguese women. Conversely, with instrumental delivery, migrant women had higher odds of episiotomy. Disparities in episiotomy were largely explained by maternity units' factors, and little by maternal and fetal characteristics.Conclusion: Our results suggest non-medically justified differential episiotomy use during childbirth and highlight the importance of developing evidence-based recommendations for episiotomy use in a country with a high frequency of medical interventions during delivery.